Ethnomatematics E-Module Development Using Problem-Based Learning to Improve Students' Problem-Solving and Self-Efficacy - Simangunsong, Ita Pratiwi (Study Program of Mathematics Education of Unimed Postgraduate Program, 2024)
This research develop a digital learning materials that implemented in Ambarita Village, situated near Lake Toba, Samosir Island, that has preserved its indigenous knowledge and traditional customs. The purpose of this study is to analyze the following: 1) the effectiveness, validity, and practicality of the PBL e-module based on Batak Toba Culture (PBL BTC), which was created to improve students' problem-solving skills at SMP Negeri 1 Simanindo; and 2) improving students' problem-solving skills through the developed e-module. The ADDIE is being used in this study. Two results were obtained from the class IX-2 test: 1) The PBL BTC e-module met the requirements of validity, effectiveness, and practicality; 2) Using the PBL BTC e-module improved problem-solving skills as demonstrated by the N-gain value of 0.506 and improved self-efficacy by the N-gain value 0.338 which places it in the